Entrepreneur as an Individual Review of Recent Literature on Entrepreneurial Skills - Normalini Md Kassim2Muhammad Salman Shabbir1, (Opción, 2019)
The purpose of this paper is to provide some rich and deep insight to explore the characteristics, traits and key features of individual Entrepreneur via comparative qualitative research methods. As a result, entrepreneurial skills required to undertake innovative endeavors are formed through the value that shaped by the social, economic and cultural aspects of being a self-employment person. In conclusion, it is probable that one can classify the set of skills can be classified as entrepreneurship skills that are distinct in nature from other leader and management skills.